PRECAUTIONARY PRINCIPLES IN INFORMATION TECHNOLOGY-BASED JOINT FUNDING SERVICES - Usanti, Trisadini Prasastinah; Nurwahjuni (jfpublisher, 2023)
Easy requirements with a fast process and no collateral required make funding through LPBBTI highly popular among the community. In addition, these activities also provide convenience, speed, and practicality in funding. Unfortunately, there are funding risks involved, such as potential defaults by fund recipients. The funding risk will be borne by the funder and the risk will be even greater if there is no collateral in the funding because the position of the funder is only as a concurrent creditor. The objective of this research is to find out precautionary principles in information technology-based joint funding services. The method used judicial normative research was conducted to understand the legal subject and legal relationship of precautionary principles in information technology-based joint funding services. Therefore, the POJK10/POJK.05/2022 does not explicitly state the precautionary principle as the basis for LPBBTI's business activities. However, it has been realized in the norms contained in POJK10/POJK.05/2022, in the form of norms that require and norms that prohibit. One of them is the obligation to conduct funding risk analysis as a risk mitigation effort. This is intended to ensure that LPBBTI develops optimally, healthily, contributively and that users' needs for optimal protection can be accommodated.